A logical structure based fault tolerant approach to handle leader election in mobile ad hoc networks - Bharti Sharma; Ravinder Singh Bhatia; Awadhesh Kumar Singh (Journal of King Saud University: Computer and Information Sciences)
We propose a light weight layered architecture to support the computation of leader in mobile ad hoc networks. In distributed applications, the leader has to perform a number of synchronization activities among participating nodes and numerous applications; hence, it is a stressed node and consequently prone to failure. Thus, fast and fault tolerant leader election is a major concern and popular area of research in distributed computing networks, in general, and wireless ad hoc networks, in particular. In the present article, we have proposed a fault tolerant leader election approach. More importantly, the nodes elect the leader quickly on the basis of local information only. The illustration includes suitable examples. The correctness proof and performance evaluation has also been presented.